The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/nu14153033
|View full text |Cite
|
Sign up to set email alerts
|

Eating Behavior Associated with Food Intake in European Adolescents Participating in the HELENA Study

Abstract: Adolescence is recognized as a time of rapid physiological and behavioral change. In this transition, eating behavior is still being formed and remains an integral part of a person’s lifestyle throughout his or her life. This study aims to assess eating behavior and associations with food intake in European adolescents. We included 2194 adolescents (45.9% boys), aged 12.5 to 17.5 years, from the cross-sectional HELENA study, with two completed 24 h recalls and complete questionnaire data on their eating behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…There are scarce data in the literature on how eating behavior affects food intake in individuals with T2DM. Most studies that analyzed dietary intake in relation to at least one of the variables of eating behavior were conducted on children and adolescents [ 72 , 73 , 74 , 75 , 76 , 77 ]. Other studies have analyzed eating behavior in relation to food intake in bariatric patients [ 78 , 79 ], patients with metabolic syndrome [ 80 ], or the general population [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are scarce data in the literature on how eating behavior affects food intake in individuals with T2DM. Most studies that analyzed dietary intake in relation to at least one of the variables of eating behavior were conducted on children and adolescents [ 72 , 73 , 74 , 75 , 76 , 77 ]. Other studies have analyzed eating behavior in relation to food intake in bariatric patients [ 78 , 79 ], patients with metabolic syndrome [ 80 ], or the general population [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data show that 95% of 12-17-year-olds in Australia (Hardy et al, 2016) and 92% of 11-18-year-olds in the United Kingdom (Huang et al, 2019) do not meet the recommended daily guidelines for fruit and vegetable intake, while 9-13-year-olds in America have a mean Healthy Eating Index dietary score of 46.85 (SD 24.93), significantly below the score of 100, that is indicatcative of meeting dietary guidelines (Banfield et al, 2016) and similar patterns have been reported in Canada (Jarman et al, 2020) and Europe (Maneschy et al, 2022). This age group also consumes the most added sugars (Statistics, 2012), with 10% of this population consuming one cup of sugar-sweetened beverages (SSB) per day (Statistics, 2014).…”
Section: Introductionmentioning
confidence: 56%